Influência do Micro-Hábitat na Estrutura do Canto de Anúncio de Hypsiboas crepitans Wied- Neuwied, 1824 (Anura: Hylidae) na Serra de São José, Feira de Santana, Bahia, e sua Relação com a Atenuação do Som - Röhr, David Lucas (2010)
Anuran vocalizations present intra and inter-specific variation, whose recognition may help at the comprehension of the evolutionary processes involved in the acoustic communication of this group of amphibians. These variations can be related to a number of factors, including the micro-habitat of vocalization, whose influence on the acoustic parameters of the advertisement calls still remains na unexplored subject. The objective of this study was to identify the influence of the micro-habitat of vocalization (inside the water and perches on the vegetation) upon the advertisement call acoustic parameters and its importance on the sound attenuation in a population of Hypsiboas crepitans which occurs at the Serra São José, northeastern Brazil. The acoustic parameters analyzed were the dominant frequency, intensity, call duration, interval between calls, and pulse rate. The acoustic parameters of the call were not related to the body size of the male and only the pulse rate was significantly influenced by the temperature. The dominant frequency and pulse rate of the advertisement call were significantly different when the frogs were calling from inside the water and at perches on the vegetation; however, there was no significant difference on the sound attenuation. The variation was detected on characteristics which are considered important in the specific recognition for anurans and that may play a main role on the sexual selection and on the efficiency of sound propagation, affecting the evolution of the species acoustic communication.